Thigh Adipocyte Size is Inversely Related to Energy Intake and Respiratory Quotient in Healthy Women. Issue 6 (30th April 2020) - Basolo, Alessio; Shah, Mujtaba H.; Parthasarathy, Varsha; Parrington, Shannon; Walter, Mary; Votruba, Susanne B.; Krakoff, Jonathan; Piaggi, Paolo; Chang, Douglas C.
Abstract : Objective: The relationship between adipocyte size and ad libitum energy intake has not been previously examined. This study hypothesized an inverse relationship between adipocyte size and daily energy intake (DEI). Methods: Seventy healthy adults (39 men and 31 women; BMI 30.0  [SD 6.3]) underwent dual‐energy x‐ray absorptiometry and subcutaneous fat biopsies from the abdomen and thigh. Osmium‐fixed adipocytes were sized with a Coulter counter. Volunteers self‐selected food from a vending machine paradigm as the only source of energy intake over 3 days as inpatients. Volunteers also had 24‐hour respiratory quotient (RQ) measured in a whole‐room indirect calorimeter. Results: In women, the large cell peak diameter of the thigh depot was greater than that of the abdominal depot (Δ = +15.8 μm; P  < 0.0001). In women, thigh peak diameter was inversely associated with DEI (β = −264.7 kcal/d per 10‐μm difference; P  = 0.03) after adjusting for demographics and body composition. The thigh peak diameter in women was associated with 24‐hour RQ ( r  = −0.47, P  = 0.04) after adjusting for demographics, body composition, and 24‐hour energy balance. These associations did not extend to men or the abdominal depot. Conclusions: In women, thigh adipocyte size was associated with reduced DEI and 24‐hour RQ, indicating a special role for thigh fat in women. This depot‐specific sexual dimorphism indicates common regulation of energy intake and adipocyte size in the thigh region of women.